Features of the use of fungicides against dry spot of potatoes - Sergienko, V.; Shyta, O.; Tkalenko, H.; Tyshchuk, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To establish the influence of fungicide application timing on the effectiveness of potato protection against early blight (Alternaria) and to assess the effectiveness of fungicides of different modes of action. Methods. Information-analytical, field research (experiment setup, fungicide treatments, recording disease incidence, harvesting), mathematical-statistical. Systemic, contact, and systemic-contact fungicides were studied on potato varieties Bellarosa and Povyn. Results. One of the most common methods of protecting potatoes from diseases during the growing season is chemical protection, which is based on the use of fungicides. Experiments with the first fungicide treatment at different times — before the appearance of the first signs of infection and with the appearance of the first symptoms — showed significantly higher protection effectiveness when treatments started prophylactically, before the symptoms appeared. The difference in fungicide effectiveness when applied before and after the appearance of symptoms averaged 29—32%, and 22% overall during the observation period. The effectiveness of the studied fungicides on the Bellarosa variety was 67.3—79.7%, and on the Povyn variety — 61.2—73.3%. The highest effectiveness on Bellarosa was shown by systemic-contact fungicides Quadris Top 325 SC, Miravis 200 SC, and Orvego SC, while on Povyn — Nativo 75 WG, Quadris Top 325 SC, and Ridomil Gold MZ 68 WG. Systemic and systemic-contact fungicides generally provided a higher protective effect compared to contact fungicides. Fungicidal protection of potatoes against early blight contributed to increased yield. On Bellarosa, the preserved yield amounted to 1.7—4.7 t/ha, and on Povyn — 5.5—7.2 t/ha depending on the fungicide. Conclusions. The use of fungicides makes it possible to effectively control the development of potato early blight during the growing season. It was proven that spraying plants before the first symptoms appear increases fungicide effectiveness on average 1.7 times. The effectiveness of systemic and systemic-contact fungicides on the studied varieties was on average 7—10% higher compared to contact fungicides. The use of fungicides contributed to an increase in potato yield by 5.4—29.2% on average, depending on the variety and the preparation.